1997
DOI: 10.1080/02701367.1997.10608008
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Performance Feedback Effectiveness through Videotape Replay and a Self-Controlled Learning Environment

Abstract: This study was designed to examine whether participants who could control the schedule of performance feedback (KP) would learn differentially from those who received a rigid feedback schedule while learning a complex task. Participants (N = 48) were randomly assigned to self-controlled KP (SELF), summary KP (SUMMARY), yoked control (YOKE), or knowledge of results only (KR) conditions. Data collection consisted of an acquisition phase and a 4-day retention phase during which right-handed participants performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
215
2
44

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 252 publications
(279 citation statements)
references
References 29 publications
18
215
2
44
Order By: Relevance
“…Wulf et al 21) reported that self-controlled feedback in an active practice was more effective at increasing practice time and learning effect than yoked feedback in a passive practice. The effectiveness of self-controlled feedback was proved by an earlier study 20) . Our results show that all the parameters of the self-controlled group concerned with balance ability were significantly smaller than those of the yoked feedback and control groups.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Wulf et al 21) reported that self-controlled feedback in an active practice was more effective at increasing practice time and learning effect than yoked feedback in a passive practice. The effectiveness of self-controlled feedback was proved by an earlier study 20) . Our results show that all the parameters of the self-controlled group concerned with balance ability were significantly smaller than those of the yoked feedback and control groups.…”
Section: Discussionmentioning
confidence: 96%
“…However, these feedback methods did not encourage active participation of the learner. To address this issue, the efficacy of self-control has been discussed in the field of recognition learning for several years 20,21,25) . The choice of tool for evaluating cognitive function is very important in the rehabilitation of cerebrovascular accident patients 33) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations